Gastric Ultrasound Assessing Gastric Emptying of Preoperative Carbohydrate Drinks: A Randomized Controlled Noninferiority Study. (15th February 2021) - Cho, Eun-Ah; Huh, Jin; Lee, Sung Hyun; Ryu, Kyoung-Ho; Shim, Jae-Geum; Cha, Yun-Byeong; Kim, Mi Sung; Song, Taejong
Abstract : BACKGROUND: Tools for the evaluation of gastric emptying have evolved over time. The purpose of this study was to show that the risk of pulmonary aspiration is not increased with carbohydrate drink, by demonstrating that the gastric antral cross-sectional area (CSA) of the NO-NPO group is either equivalent to or less than that of the NPO (nil per os) group. METHODS: Sixty-four patients scheduled for elective laparoscopic benign gynecologic surgery were enrolled and randomly assigned to the NPO group (n = 32) or the NO-NPO group (n = 32). After having a regular meal until midnight before surgery, the NPO group fasted until surgery, while the NO-NPO group ingested 400 mL of a carbohydrate drink at midnight and freely up to 2 hours before anesthesia. The primary outcome was the gastric antral CSA by gastric ultrasound in right lateral decubitus position (RLDP). Noninferiority was defined as a mean difference of CSA <2.8 cm 2 . Secondary outcomes included CSA in supine position, gastric volume (GV), GV per weight (GV/kg), GV/kg >1.5 mL/kg, and Perlas grade. RESULTS: CSA in RLDP was not different between the NPO group (6.25 ± 3.79 cm 2 ) and the NO-NPO group (6.21 ± 2.48 cm 2 ; P = .959). The mean difference of CSA in RLDP (NO-NPO group − NPO group) was 0.04 (95% confidence interval [CI], −1.56 to 1.64), which was within the noninferiority margin of 2.8 cm 2 . CSA was not different between the 2 groups (4.17 ± 2.34 cm 2 in NPO group versus 4.28 ± 1.23 cm 2 in NO-NPO group; P = .828). GV in NPO group (70 ± 56 mL) was not different from NO-NPO group (66 ± 36 mL; mean difference, 3.66; 95% CI, −20 to 27; P = .756). GV/kg in the NPO group (1.25 ± 1.00 mL/kg) was not different from the NO-NPO group (1.17 ± 0.67 mL/kg; P = .694). The incidence of GV/kg > 1.5 mL/kg was not different between NPO (31.3%) and NO-NPO group (21.9%; P = .768). The median (interquartile range) of the Perlas grade was 1 (0–1) in NPO group and 0.5 (0–1) in NO-NPO group ( P = .871). CONCLUSIONS: Preoperative carbohydrates ingested up to 2 hours before anesthesia do not delay gastric emptying compared to midnight fasting, as evaluated with gastric ultrasound.